Advances in Computational Biology Proceedings of the 2nd Colombian Congress on Computational Biology and Bioinformatics (CCBCOL) - Castillo, Luis F.; Cristancho, Marco; Isaza, Gustavo; Pinzón, Andrés; Rodríguez, Juan Manuel Corchado (Advances in Intelligent Systems and Computing,, 2014)
This volume compiles accepted contributions for the 2nd Edition of the Colombian Computational Biology and Bioinformatics Congress CCBCOL, after a rigorous review process in which 54 papers were accepted for publication from 119 submitted contributions. Bioinformatics and Computational Biology are areas of knowledge that have emerged due to advances that have taken place in the Biological Sciences and its integration with Information Sciences. The expansion of projects involving the study of genomes has led the way in the production of vast amounts of sequence data which needs to be organized, analyzed and stored to understand phenomena associated with living organisms related to their evolution, behavior in different ecosystems, and the development of applications that can be derived from this analysis.  .